2017
DOI: 10.1128/aem.01564-17
|View full text |Cite
|
Sign up to set email alerts
|

Use of Endophytic and Rhizosphere Actinobacteria from Grapevine Plants To Reduce Nursery Fungal Graft Infections That Lead to Young Grapevine Decline

Abstract: Endophytic and rhizosphere actinobacteria isolated from the root system of 1-year-old grafted Vitis vinifera plants were evaluated for their activities against fungi that cause grapevine trunk diseases. A total of 58 endophytic and 94 rhizosphere isolates were tested. Based on an in vitro bioassay, 15.5% of the endophytic isolates and 30.8% of the rhizosphere isolates exhibited antifungal activity against the fungal pathogen Diplodia seriata, whereas 13.8% of the endophytic isolates and 16.0% of the rhizospher… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
93
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 98 publications
(98 citation statements)
references
References 47 publications
4
93
1
Order By: Relevance
“…More recently, Halleen and Fourie concluded that T. harzianum performed better against natural black‐foot infections in an integrated strategy in the propagation process combined with chemical treatment and/or HWT than in repeat treatments of the same product. Other BCAs have been tested against black‐foot disease pathogens with promising results . Inoculation of roots with the mycorrhizal fungus Rhizophagus irregularis (syn.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…More recently, Halleen and Fourie concluded that T. harzianum performed better against natural black‐foot infections in an integrated strategy in the propagation process combined with chemical treatment and/or HWT than in repeat treatments of the same product. Other BCAs have been tested against black‐foot disease pathogens with promising results . Inoculation of roots with the mycorrhizal fungus Rhizophagus irregularis (syn.…”
Section: Discussionmentioning
confidence: 99%
“…Glomus intraradices ) reduced the disease severity caused by black‐foot disease pathogens . Also, application of actinobacteria to grafted plant roots, selected for their in vitro antifungal properties against black‐foot disease pathogens, resulted in a significant decrease in fungal infection in nursery fields …”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Many attempts have been made to understand the origin of the Pch inoculum, and numerous potential sources of the fungus have been suggested, but its epidemiology is still unclear. This fungus is considered an air-borne and water-splashed pathogen , and its main infection of grapevine is reported to occur through wounds caused by intensive pruning, hydric stress, frost or other mechanical injuries such as grafting (Agustí-Brisach, León, Garcia-Jimenez, & Armengol, 2015;Larignon & Dubos, 2000).…”
Section: Introductionmentioning
confidence: 99%